Kulturowa teoria kapitalizmu - Tudek, Andrzej (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2004)
The paper is an extensive critique of a book by P.L. Berger, entitled The Capitalist Revolution and devoted to the non-economic conditions of capitalism spreading throughout the world. The author reflects on the issue whether the research method presented in the book, written at the time of confrontation between capitalism and socialism, remains efficient in the contemporary world facing quite different challenges. The answer is negative, as the author proves that Berger proposed an interesting idea of researching the so-called economic culture, but he failed to develop it as he neglected appropriate definitions. Consequently, Berger’s considerations devoted to the peculiarity of Western European culture are narrowed to the historic analyses of the influence of religion and social myths on common awareness. The author of the paper rejects the suggestion that the tension between the traditional middle class and intellectuals may threaten the vitality of capitalism.